ANALISIS PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PERBANKAN (Studi Kasus Perusahaan Perbankan yang Tercatat di Bursa Efek Indonesia Periode 2018-2020) - Susanti Budiastuti; Sri Hartati; Suseno (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
The research entitled “Analysis of the Effect of Financial Ratios on Banking Financial Performance (Case Study of Banking Companies Listed on the Indonesia Stock Exchange for the Period 2018-2020). The financial ratios used are Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), while financial performance is measured by the Return on Assets (ROA) ratio. The formulation of the research problem is the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan Deposit Ratio (LDR), have an effect on Return on Assets (ROA). This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), on Return on Assets (ROA). This research is a quantitative research using secondary data Data in the form of annual financial statements of banking companies listed on the IDX for the period 2008-2020, obtained a sample of 18 companies based on the purposive sampling method. The analytical technique used is multiple linear regression analysis and to determine the accuracy of the model, the classical assumption test is carried out. The results showed that the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) had a significant positive effect on Return on Assets (ROA) while Non Performing Loans (NPL) had a significant negative effect on Return on Assets (ROA). It is proven by the CAR tcount (2.443) and LDR (5.825) which is greater than the ttable value (2.009) and the NPL tcount value (-4.207) is smaller than the ttable value (-2.009), with sig. value CAR (0.018), NPL (0.000), LDR (0.000) < a (0.05).